The Monetary Costs of Criminal Trajectories for a Sample of Offenders in Ontario, Canada - Day, David M. (Journal of developmental and life-course criminology, 2019)
Purpose: The past 20 years have seen an increase in the number of studies on the monetary costs of crime. More recently, researchers have turned to trajectory analysis to derive longitudinal cost estimates to generate more precise figures across subgroups of offenders. This approach is thought to provide policy makers with more nuanced information for informed decision-making about the targeted allocation of limited resources. The present study adds a Canadian perspective to the literature by providing cost estimates for seven criminal trajectory groups generated for a sample of male offenders in Ontario, Canada, based on their longitudinal pattern of offending from ages 12 to 26 years. Methods: The study sample consisted of 386 individuals who had been sentenced between 1986 and 1997 as juvenile offenders to one of two open custody facilities in Toronto. Costs included victim-related costs, disposition-related correctional costs, other criminal justice costs, and costs of undetected crimes. Results: The total aggregate, longitudinal cost of offending was 2.26 billion, or an average of 5,855,318 per person. Across the seven trajectories, average costs varied from a low of 3,546,154 per person in the low desister group to a high of 16,954,604 per person in high late group. Conclusions: Given the high monetary costs incurred by crime victims, the correctional system, and by other aspects of the criminal justice system, investments in crime prevention programs for those at risk for a high highrate criminal trajectory are likely to yield long-term cost savings. Similarly, prevention efforts aimed at moderate or even lower-risk groups may also yield positive benefit-to-cost ratios with effective, targeted interventions.